Validity of Myobradypterygius hauthali von Huene, 1927 (Ichthyosauria Ophthalmosauria) from the early cretaceous of Chile and Argentina - Pardo-Pérez, Judith; Zambrano, Patricio; Malkowski, Matthew; Lomax, Dean; Villa-Martínez, Rodrigo; Stinnesbeck, Wolfgang; Frey, Eberhard; Scapini, Francisca; Gascó, Cristina; Maxwell, Erin E (Zoological journal of the Linnean Society, 2024)
Early Cretaceous ichthyosaurs were globally distributed pelagic marine reptiles, but many remains are fragmentary, creating a Northern Hemisphere diversity bias. A rich Hauterivian locality near the Tyndall Glacier inside Torres del Paine National Park in southern Chile yields important new data regarding ichthyosaurian diversity along the Pacific margin of Gondwana. These new data will contribute to clarifying questions regarding ichthyosaur taxonomy and the palaeobiogeographical relationships between the southern Gondwanan and Northern Hemisphere ichthyosaur groups during the Early Cretaceous. Here, we describe three new ichthyosaur specimens from this locality. Two of them are referred to Myobradypterygius hauthali, expanding the distribution of this species from the Barremian of Argentina to the Hauterivian of the Chilean Patagonia. This material shows that M. hauthali differs from Platypterygius platydactylus in forefin construction and scapular morphology, supporting its classification as a separate genus within Platypterygiinae. The third specimen is a large-bodied indeterminate ophthalmosaurine ichthyosaur. This record represents the southernmost record of Ophthalmosaurinae and the first occurrence of this group from the Cretaceous of the Southern Hemisphere. These discoveries show that ophthalmosaurines and platypterygiines continued to occur sympatrically in southernmost Gondwana during the Early Cretaceous, expanding the pattern documented in Europe to the Pacific region.
Gesehen am 17.06.2025